Mistakes in the treatment of pterygium (Ukrainian Journal of Ophthalmology, 2025)
Abrupt thinning and even perforation at the limbus and cornea due to deep pterygium excision are potential postoperative complications of pterygium syrgery. Postoperative complications were observed in 25.7% of patients after primary pterygium excision. The analysis of mistakes made in the surgical treatment of pterygium enabled the following recommendations to be made. First, pterygium should be excised with minimal trauma to the limbus and cornea. Second, the patient should be promptly referred to the medical facility at which he/she can undergo keratoplasty if complications (perforations and/or ulcers) develop during pterygium excision. Third, a patient’s concomitant autoimmune disease should be taken into account. Fourth, one should not perform bilateral pterygium surgery or repeat pterygium excision early (? 6 months) after primary pterygium surgery. Finally, steroid and antimetabolic therapy, barrier and optic lamellar keratoplasty, and amniotic membrane transplantation should be used to prevent pterygium recurrence.
Keywords: pterygium; treatment; mistakes